Host country-specific factors causing outwards foreign direct investment from Malaysia - Andaman, Gul; Yusop, Zulkornain; Mohd Noor, Zaleha; Kaliappan, Shive Ranjanee (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study analyzes macroeconomic and institutional factors of the host countries in attracting outwards foreign direct investment (OFDI) from Malaysia. Results show that primary motives behind Malaysian OFDI are to seek growing markets and natural resources. Foreign economy’s depreciating currency with respect to Ringgit Malaysia, lower private sector lending rate, shorter geographical distance from Malaysia and government accountability are also important pull factors. Malaysian OFDI is significantly low in ASEAN Member States (AMS) and in the developed states. Policy implications thus include generation of higher OFDI towards AMS given the strategic importance of ASEAN Economic Community and in developed regions to access foreign technology.